PENGARUH CITRA MEREK DAN HARGA TERHADAP MINAT BELI PRODUK MIE INSTAN (Studi Pada Siswa SMA Negeri 1 Kuala Kapuas) - Sunarmi . sunarmi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
With market competition, one of the strategies used by companies to maintain their business is brand strategy. Price is also a determinant in consumer buying interest in the products offered from producers. By improving the brand quality of the product and producers can also promote these products using electronic media and social media, it can attract attention and with the quality of the brand. The purpose of this study was to determine the effect of brand image and price on buying interest in indomie. This study uses quantitative methods using a questionnaire. The data used used multiple linear regression analysis. The sample used was all SMA Negeri 1 Kuala Kapuas students with a population of 75 people. The results of data analysis show that there is an effect of brand image and price with a significant value of 0.000 or below 5% (0.05). The conclusion from the results of this study is that there is a positive and significant influence on buying interest in indomie.